Abnormal accumulation of autophagic vesicles correlates with axonal and synaptic pathology in young Alzheimer’s mice hippocampus. - Sánchez-Varo, Raquel María; Trujillo-Estrada, Laura Isabel; Sánchez-Mejías, Elisabeth; Torres, Manuel; Baglietto-Vargas, David; Moreno-González, Inés; De Castro, Vanessa; Jiménez, Sebastián; Ruano, Diego; Vizuete, Marisa; Dávila-Cansino, José Carlos; García-Verdugo, José Manuel; et al. (Springer Nature, 2012)
Dystrophic neurites associated with amyloid plaques precede neuronal death and manifest early in Alzheimer’s disease (AD). In this work we have characterized the plaque-associated neuritic pathology in the hippocampus of young (4- to 6-month-old) PS1M146L/APP751SL mice model, as the initial degenerative process underlying functional disturbance prior to neuronal loss. Neuritic plaques accounted for almost all fibrillar deposits and an axonal origin of the dystrophies was demonstrated. The early induction of autophagy pathology was evidenced by increased protein levels of the autophagosome marker LC3 that was localized in the axonal dystrophies, and by electron microscopic identification of numerous autophagic vesicles filling and causing the axonal swellings. Early neuritic cytoskeletal defects determined by the presence of phosphorylated tau (AT8-positive) and actin–cofilin rods along with decreased levels of kinesin-1 and dynein motor proteins could be responsible for this extensive vesicle accumulation within dystrophic neurites. Although microsomal amyloid-beta oligomers were identified, the presence of A11-immunopositive amyloid plaques also suggested a direct role of plaque-associated amyloid-beta oligomers in defective axonal transport and disease progression. Most importantly, presynaptic terminals morphologically disrupted by abnormal autophagic vesicle buildup were identified ultrastructurally and further supported by synaptosome isolation. Finally, these early abnormalities in axonal and presynaptic structures might represent the morphological substrate of hippocampal dysfunction preceding synaptic and neuronal loss and could significantly contribute to AD pathology in the preclinical stages.
Keywords: Alzheimer, Enfermedad de - Modelos animales; Desarrollo neurológico; Hipocampo (Cerebro); PS1/APP transgenic mice; Dystrophic neurites; LC3; Amyloid plaques; Electron microscopy; Presynaptic terminals